Yoga, cognitive–behavioural therapy versus education to improve quality of life and reduce healthcare costs in people with endometriosis: a randomised controlled trial. Issue 8 (9th August 2021) - Mikocka-Walus, Antonina; Druitt, Marilla; O'Shea, Melissa; Skvarc, David; Watts, Jennifer J; Esterman, Adrian; Tsaltas, Jim; Knowles, Simon; Harris, Jill; Dowding, Charlotte; Parigi, Elesha; Evans, Subhadra
Abstract : Introduction: Endometriosis is a debilitating chronic inflammatory condition highly burdensome to the healthcare system. The present trial will establish the efficacy of (1) yoga and (2) cognitive–behavioural therapy (CBT), above (3) education, on quality of life, biopsychosocial outcomes and cost-effectiveness. Methods and analysis: This study is a parallel randomised controlled trial. Participants will be randomly allocated to yoga, CBT or education. Participants will be English-speaking adults, have a diagnosis of endometriosis by a qualified physician, with pain for at least 6 months, and access to internet. Participants will attend 8 weekly group CBT sessions of 120 min; or 8 weekly group yoga sessions of 60 min; or receive weekly educational handouts on endometriosis. The primary outcome measure is quality of life. The analysis will include mixed-effects analysis of variance and linear models, cost–utility analysis from a societal and health system perspective and qualitative thematic analysis. Ethics and dissemination: Enrolment in the study is voluntary and participants can withdraw at any time. Participants will be given the option to discuss the study with their next of kin/treating physician. Findings will be disseminated via publications, conferences and briefs to professional organisations. The University's media team will also be used to further disseminate via lay person articles and media releases. Trial registration number: ACTRN12620000756921p; Pre-results.